Low awareness of risk mitigation prescribing in response to dual crises of COVID-19 and overdose deaths among people who use unregulated drugs in Vancouver, Canada - Mana Moshkforoush; Kora DeBeck; Rupinder Brar; Nadia Fairbairn; Zishan Cui; M.-J. Milloy; Jane Buxton; Tanis Oldenburger; Will McLellan; Perry Kendall; Kali Sedgemore; Dean Wilson; et al. (BMC, 2022)
Abstract Background When the novel coronavirus pandemic emerged in March 2020, many settings across Canada and the USA were already contending with an existing crisis of drug overdoses due to the toxic unregulated drug supply. In response, the Canadian province of British Columbia (BC) released innovative risk mitigation prescribing (RMP) guidelines for medical professionals to prescribe pharmaceutical alternatives to unregulated drugs in an effort to support the self-isolation of people who use unregulated drugs (PWUD) in preventing both SARS-CoV-2 virus infection and overdoses. We sought to assess the level of awareness of RMP and identify factors associated with this awareness among PWUD in Vancouver, BC. Methods Cross-sectional data were derived from participants enrolled in three community-recruited prospective cohort studies of PWUD in Vancouver, interviewed between July and November 2020. Multivariable logistic regression analysis was used to identify factors associated with awareness of RMP. Results Among 633 participants, 302 (47.7%) had heard of RMP. Of those 302 participants, 199 (65.9%) had never tried to access RMP services, ten (3.3%) made an unsuccessful attempt to access RMP, and 93 (30.8%) received RMP. In the multivariable analysis, participants who had awareness of RMP guidelines were more likely to self-identify as white (adjusted odds ratio [AOR] = 1.47; 95% confidence interval [CI]: 1.01, 2.13), to have completed secondary school education or higher (AOR = 1.67; 95% CI: 1.16, 2.39), to have used drugs at a supervised consumption or overdose prevention site in the past six months (AOR = 1.66; 95% CI: 1.10, 2.52), and to have received opioid agonist therapy as treatment for opioid use disorder in the past six months (AOR = 1.51; 95% CI: 1.02, 2.24). Conclusion At least four months after the release of the guidelines, RMP was known to less than half of our study participants, warranting urgent educational efforts for PWUD, particularly among racialized groups and those who were not accessing other harm reduction services. Furthermore, the majority of participants who were aware of RMP guidelines had never tried to access the service, suggesting the need to improve perceived accessibility and knowledge of eligibility criteria.